2012
DOI: 10.1155/2012/514242
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of the Electrokinetic Theory and Development of Seismoelectric Interferometry by Cross-Correlation

Abstract: We experimentally validate a relatively recent electrokinetic formulation of the streaming potential (SP) coefficient as developed by Pride (1994). The start of our investigation focuses on the streaming potential coefficient, which gives rise to the coupling of mechanical and electromagnetic fields. It is found that the theoretical amplitude values of this dynamic SP coefficient are in good agreement with the normalized experimental results over a wide frequency range, assuming no frequency dependence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 75 publications
(168 reference statements)
3
26
0
Order By: Relevance
“…Moreover Schoemaker et al (2012) showed that the theoretical amplitude values of the dynamic streaming potential coefficient are in good agreement with their normalized experimental results over a wide frequency range, without assuming a frequency dependence of the bulk conductivity. More details on the frequency-dependent streaming potentials are provided by the review of Jouniaux and Bordes (2012) including a description of different experimental apparatus.…”
Section: Frequency-dependence Electrokineticssupporting
confidence: 63%
“…Moreover Schoemaker et al (2012) showed that the theoretical amplitude values of the dynamic streaming potential coefficient are in good agreement with their normalized experimental results over a wide frequency range, without assuming a frequency dependence of the bulk conductivity. More details on the frequency-dependent streaming potentials are provided by the review of Jouniaux and Bordes (2012) including a description of different experimental apparatus.…”
Section: Frequency-dependence Electrokineticssupporting
confidence: 63%
“…The flow transports excess electrical charge in the so-called electrical double layer (Stern, 1924). We refer to the net flow of charge relative to the grains as the streaming electric current (Schoemaker et al, 2012). This induced conduction current leads to the first type of seismic-to-electric coupling: the coseismic field.…”
Section: Theorymentioning
confidence: 99%
“…It travels along with the seismic wave and hence with seismic velocities. However, when this wave hits an interface with changing mechanical, hydraulic or electrical properties, this results in a local asymmetry in the charge distribution (Schoemaker et al, 2012), therefore creating an effective electromagnetic dipole source at the interface (Thompson and Gist, 1993). This generates an independently diffusing electromagnetic field that will arrive almost instantaneously at the receiver level, since its velocity is several orders of magnitude higher than the seismic wave velocities.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some research has been performed on seismoelectric phenomena, where coupled seismic waves and electromagnetic fields are considered together (e.g, Pride (1994), Haartsen and Pride (1997), Revil et al (2007)). The seismoelectric effect can be of importance for hydrocarbon exploration as it is complementary to conventional seismics (e.g., Thompson and Gist (1993), Schoemaker et al (2012)). Seismoelectric fields can provide us with both seismic (Biot's poroelasticity equations) and electromagnetic (Maxwell's electromagnetic equations) sensitivities that are coupled to each other via a coupling coefficient (Pride (1994), Pride and Haartsen (1996)).…”
Section: Introductionmentioning
confidence: 99%